A new species of ant mimicking spider, Myrmecotypus jasmineae (Araneae: Corinnidae: Castianeirinae), from Nicaragua - Leister, Matthew; Miller, Kelly (Zootaxa, 2014)
Spiders of the corinnid genus Myrmecotypus Pickard-Cambridge, 1894 are known for being morphological and behavioral mimics of ants (Reiskind 1969, 1977; Cushing 1997, 2012; Rubio & Arbino 2009; Rubio et al. 2013). This genus currently includes nine species from to the New World. They occur from the United States (one species) to Argentina (one species), but most (seven species) occur from Mexico to Panama (Reiskind 1969; Rubio & Arbino 2009, Platnick 2014). A new species, M. jasmineae, from Nicaragua is described here from two males. A key to males and females of Myrmecotypus, adapted from Reiskind (1969), is modified to include all of the known species.